Residual Log-Periodogram Inference for Long-Run Relationships - Uwe Hassler; Francesc Marmol; Carlos Velasco (Technische Universität Darmstadt, Department of Law and Economics, 2002)
We assume that some consistent estimator of an equilibrium relation between non-stationary fractionally integrated series is used in a first step to compute residuals (or differences thereof). We propose to apply the semiparametric log-periodogram regression to the (differenced) residuals in order to estimate and test the degree of persistence of the equilibrium deviation. Provided the first step estimator converges fast enough, we describe simple semiparametric conditions around zero frequency that guarantee consistent estimation of persistence from residuals. At the same time limiting normality is derived, which allows to construct approximate confidence intervals to test hypotheses on the persistence. Our assumptions allow for stationary deviations with long memory as well as for non-stationary but transitory equilibrium errors. In particular, in case of several regressors we consider the joint estimation of the memory parameters of the observed series and of the equilibrium deviation. Wald statistics to test for parameter restrictions of the system have a limiting chi-squared distribution. We also analyze the benefits of a pooled version of the estimate. The empirical applicability of our general cointegration test is investigated by means of Monte Carlo experiments and illustrated with a study of exchange rate dynamics
Keywords: C14; C22; 330; Fractional cointegration; semiparametric inference; limiting normality; long memory; non-stationarity; exchange rates; Kointegration; Zeitreihenanalyse; Nichtparametrisches Verfahren; Deskriptive Statistik; Theorie; Inferenzstatistik